Jak powstawała korbutowa bibliografia Adama Mickiewicza? - Przychodniak, Zbigniew (Biblioteka Uniwersytecka w Poznaniu, 2017)
Ranga i zakres twórczości Adama Mickiewicza określają potrzebę i znaczenie opracowań bibliograficznych obejmujących twórczość i literaturę przedmiotową autora Dziadów i Pana Tadeusza. Początki bibliografii Mickiewiczowskich sięgają lat 40. XIX wieku; w drugiej połowie XIX i na początku XX wieku powstało wiele bibliografii cząstkowych. Zainicjowana przez Gabriela Korbuta w 1917 roku bibliografia literatury polskiej stała się po roku 1950 podstawą do stworzenia nowej, pełniejszej redakcji w postaci 19-tomowej serii bibliografii poszczególnych epok i wybranych pisarzy. Trwający dziesięciolecia proces przygotowywania i opracowywania dla serii „Nowego Korbuta” zaplanowanego tomu 10 poświęconego Mickiewiczowi przyniósł realizację pierwszej części (literatury podmiotowej) i daje szansę na stworzenie jego nowoczesnej mutacji w formie internetowej strony Bibliografii Mickiewiczowskiej.

Adam Mickiewicz in the Bibliography of Polish Literature of G. Korbut Abstract. The significance and scope of literary output of Adam Mickiewicz determines the need and importance of its bibliographical coverage and studies on the source literature pertaining to the author of Forefathers’ Eve and Pan Tadeusz. The beginnings of bibliographies devoted to Mickiewicz rest as early as the 1840s; in the latter half of the 19th c. and the beginning of the 20th c. a great number of partial and incomprehensive bibliographies originated. The bibliography of Polish literature, initiated by Gabriel Korbut in 1917, provided, after 1950, a base for a new and more comprehensive edition finalised in the 19-volume strong series of bibliographies for individual literary epochs and selected authors. The process of preparation and edition of the planned Volume 10, entirely devoted to Mickiewicz and aimed to be included in the series Nowy Korbut (A New Korbut Bibliography of Polish Literature), has taken decades to complete its first part (bibliographic listings) and provides an opportunity to create its state-of-the-art mutation in the form of a digital edition of the Mickiewicz bibliography available online.
Adam Mickiewicz in the Bibliography of Polish Literature of G. Korbut
Keywords: bibliografia literacka; Adam Mickiewicz; „Nowy Korbut”; literary bibliography; A New Korbut Bibliography of Polish Literature